Development of technology for canning of ringed seal meat - L. V. Shulgina; T. A. Davletshina; A. E. Кarlina; K. G. Pavel’; E. A. Solodova (Известия ТИНРО, 2020)
Results of studies on technology of natural canned meat of ringed seal (akiba) are presented. The frozen seal meat was used for canning without subcutaneous fat that was removed after slaughter. Protein content in the muscle tissue was 22.50 ± 0.71 %, fat content — 8.20 ± 0.20 %, minerals — 1.20 ± 0.10 %, its energy value was 167.4 ± 5.6 kcal/100 g. After defrosting, pieces of the seal meat were kept in fresh water at temperature of 15–18 oC for 2 to 3 hours, then onion and flavorings were added. The spiced meet was packed to cans № 6 and sterilized under temperature of 120 oC. The finished canned food had a meaty taste and smell, without extraneous smacks and smells. The broth was transparent with brown tint and small amount of suspended protein substances. Protein content in the finished canned food was 17.0 %, fat content 7.0 %, protein composition was close to the standard protein by amount and ratio of essential amino acids. Monounsaturated fatty acids dominated in lipids of the canned food (58.08 % of total lipids), mainly oleic (18:1 n-9) and palmitooleic (16:1 n-7) acids; portion of polyunsaturated fatty acids was 22.17 %, including omega-3 fatty acids (18.56 % of PUFA). High content of iron (6.6 mg/100 g), zinc (2.3 mg/100 g) and selenium (80 μg/100 g) was detected in the canned food that partially or completely maintained daily requirements of human body for these elements.